1986
DOI: 10.1111/j.1600-0714.1986.tb00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical demonstration of keratin proteins in duct‐ligated salivary glands of mice and rats

Abstract: Immunohistochemical detection of keratin proteins in duct‐ligated submandibular glands (SMG) was carried out in mice and rats with or without testosterone administration. Keratin staining in normal salivary glands was limited to the striated duct (SD) and excretory duct (ED) cells and was usually lacking in granular convoluted tubule (GCT) cells. Following duct‐ligation, the epithelia of intercalated ducts (ICD), degranulated tubules, duct‐like structures, and dilated striated and excretory ducts showed positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Histologic and immunohistochemical studies of EGF and NGF following duct-ligation of SMGs in mice and rats, show initial changes include the degranulation of GCT cells and the disappearance or a reduction in staining for growth factors in GCT segments (6). It has also been reported that keratin protein is expressed in duct-Uke structures of the duct-ligated SMG, though normal GCT cells are usually devoid of keratin staining (7). In duct-ligated SMGs, immunostaining for growth factor was reduced with the simultaneous appearance of keratin staining in degranulated cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologic and immunohistochemical studies of EGF and NGF following duct-ligation of SMGs in mice and rats, show initial changes include the degranulation of GCT cells and the disappearance or a reduction in staining for growth factors in GCT segments (6). It has also been reported that keratin protein is expressed in duct-Uke structures of the duct-ligated SMG, though normal GCT cells are usually devoid of keratin staining (7). In duct-ligated SMGs, immunostaining for growth factor was reduced with the simultaneous appearance of keratin staining in degranulated cells.…”
Section: Discussionmentioning
confidence: 99%
“…detected changes in keratin protein expression have been observed in experimentally obstructed salivary glands in the mouse, rat and cat (1)(2)(3)(4)(5)(6)(7). The granular convoluted tubule (GCT) cells in the mouse submandibular gland (SMG) contains a characteristic abundance of epidermal growth factor (EGF) and nerve growth factor (NGF) (8)(9)(10)(11)(12), and conspicuous changes occur in the quantity of EGF and NGF deposition following duct ligation (6).…”
Section: Various Pathologic Changes Including Iitimunohistochemicallymentioning
confidence: 99%
“…Regarding histochemical examination of duct-ligated SMGs; in duct-ligated SMGs with testosterone treatment and in those with testosterone in castrated mice, immunohistochemically detectable EGF for marking GCT cells (1,8,9,15,17,24,26), keratin (KLIM) proteins for marking duct cells (4,6,19,23,26,27), PNA and SBA lectin binding for marking GCT cells and DBA lectin for that of acinar elements, have been reported (16,20,25,26). From both histologic and immunohistochemical features in duct-ligated SMGs and castration which treated variable regimens of testosterone treatment, biologic response to testosterone in GCT cells of duct-ligated SMGs could be obtained significantly.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been pointed out that immunohistochemically detectable epidermal growth factor (EGF) and nerve growth factor (NGF) in the GCT cells in this alterative progress of ligated SMGs were markedly reduced when followed by ligation (24), whereas keratin (KLIM) gradually developed in degranulated GCT cells, and lectin binding affinities in acinar and GCT cells were changed depending on histologic figures (26,27). GCT cells in mice submandibular glands (SMGs) are unique structures containing a lot of growth factors (EGF and NGF etc.)…”
mentioning
confidence: 99%
“…Additionally, Hashimoto et al showed that the negative expression of epidermal growth factor (EGF), nerve growth factor (NGF), and S-100 protein in duct obstructions leads to a reduction or elimination of the function of granular ductal cells. The loss of S-100 and EGF expression after ligation further indicated that the granular duct had lost its ability to repair, resulting in decreased tissue regeneration ( Takai, et al, 1985 ; Takai, et al, 1986 ; Hashimoto, et al, 1992 ). Few studies have been conducted on salivary gland duct ligation injury to date, and it is unclear which signaling pathway is activated.…”
Section: Salivary Gland Duct Ligationmentioning
confidence: 99%